Presumptive Taxation : Revenue and Automatic Stabilizer Aspects - Erbas, S. (IMF Working Papers; Working Paper ;, 1993)
Presumptive taxation has been adopted in many countries to tax hard-to-tax activities and reduce evasion. Further, in view of the possible efficiency gains from such techniques, a case can be made for adopting presumptive taxation of global income. This paper addresses two questions. First, could revenue be increased by adopting presumptive tax methods? Second, would presumptive income taxation contribute to macroeconomic instability because it lacks the automatic stabilizer property of standard progressive income taxation? Two simple models suggest that there is scope for increasing revenue under presumptive taxation without necessarily undermining economic stability. The relevance of the first model for presumptive excise taxation in Pakistan is also examined.